2009
DOI: 10.1007/s10147-009-0878-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stage IVB endometrial carcinoma patients with distant metastasis: a review of prognoses in 55 patients

Abstract: For operable patients, surgery as an initial treatment and reduction of the residual tumor size to less than 2 cm appeared to contribute to a better prognosis. In addition, conservative initial treatment and the presence of non-lung hematogenous metastasis were poor prognostic factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 18 publications
1
9
0
Order By: Relevance
“…Lung metastasis was associated with better survival than brain metastasis, although no significant differences were observed when lung, liver, and bone metastases were compared. This result is partly consistent with that of Numazaki et al, 20 who reported that lung metastasis was associated with a better prognosis than non-lung hematogenous metastasis. Their observation may be related to the fact that women with brain metastasis were included in the group of women with non-lung hematogenous metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Lung metastasis was associated with better survival than brain metastasis, although no significant differences were observed when lung, liver, and bone metastases were compared. This result is partly consistent with that of Numazaki et al, 20 who reported that lung metastasis was associated with a better prognosis than non-lung hematogenous metastasis. Their observation may be related to the fact that women with brain metastasis were included in the group of women with non-lung hematogenous metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, EC patients with equivalent FIGO stages may have different prognoses, which may require different treatment strategies. Metastasis is relatively uncommon in patients with EC; therefore, only a small number of studies have evaluated the prognosis impact of different metastatic sites 7‐9 . However, these studies have focused on the description of a single metastatic site without comparing the survival impact of different metastasis sites.…”
Section: Introductionmentioning
confidence: 99%
“…Cardiac myocytes are proliferative in the fetal heart but soon after birth ventricular myocytes become terminally differentiated and bi-nucleated and lose their ability to reenter the cell cycle [1315]. There is an association between fetal myocyte proliferation and the presence of TTCCs and the reduced expression of TTCCs after birth is associated with the exit of ventricular myocytes from the cell cycle.…”
Section: Introductionmentioning
confidence: 99%